KUALITAS HARDBOARD DUA JENIS BAMBU DENGAN TAMBAHAN TANIN RESORSINOL FORMALDEHIDA - Dian Anggraini Indrawan; I.M. Sulastiningsih; Rossi Margareth Tampubolon; Gustan Pari; Adi Santoso (BRIN Publishing, 2017)
All kinds of ligno-cellulose fiber stuffs are technically suitable for hardboard manufacture. In Indonesia, currently the available conventional ligno-cellulose fibers (esp. tropical natural-forest woods) become scarce and depleted. Meanwhile, domestic fiberboard-production is lower than its demands. Alternative fibers, abundantly potential and largely still unutilized, should be introduced, e.g. bamboo. Research on bamboo utilization for hardboard has been carried out using two bamboo species i.e. tali bamboo (Gigantochloa apus) and ampel bamboo (Bambusa vulgaris). Each bamboo species was pulped using open hot-soda semi-chemical process. Five proportions of bamboo pulp mixtures were prepared from tali-bamboo pulp and ampel-bamboo pulps i.e: 100%+0%, 75%+25%, 50%+50%, 25%+75%, and 0%+100%. Tannin-resorcinol-formaldehyde (TRF) adhesive was added to each bamboo pulp mixtures at three different resin contents, i.e. 0%, 6% and 8% based on dry weight of the bamboo pulp mixture. Bamboo hardboards were manufactured using wet forming process and the resulted boards were then tested for their physical and mechanical properties. Results showed that addition of TRF (up to 8%) improved hardboard properties. Hardboard made from the ampel-bamboo pulp (100%) produced the highest hardboard quality, as its properties mostly conform with the standards (JIS and ISO) requirements for density, modulus of elasticity (MOE), modulus of rupture (MOR) and internal bond (IB); while hardboards made from tali-bamboo pulp (100%) possessed the lowest quality. Hardboard from tali-bamboo pulp and ampel-bamboo pulp mixture (at 50%+50% and 25% + 75% proportions) afforded the second and third performances. The least prospective tali-bamboo pulp (100%) could expectedly be improved by using more TRF.